The engineering geological behaviour of disturbed and weatherd gneiss in slopes. The case of the "vertical axis" of Egnatia motorway, Komotini - Nymfea, Northern Greece. - Marinos, V.; Goricki, A. (Bulletin of the Geological Society of Greece, 2013)
Sound gneiss forms evidently very competent rock masses with minor problems in geotechnical works. However, poor rock masses and problematic behaviour can be encountered in engineering projects in a geological environment characterized by intensive and sequent tectonic disturbance, where, weathering may be strongly favoured. Case studies with slope instability problems are analysed from the Egnatia Motorway along the vertical axis from Komotini to Nymfea, in Northern Greece. The basic engineering geological consideration focuses on the weathering degree, the tectonic disturbance, the foliated structure and the presence of shear zones. In the paper the gneissic rock masses are categorized in a number of specific rock mass types according to key engineering geological characteristics that define the rock mass behaviour in slopes. Subsequently, the slope behaviour of each rock mass type is discussed. The geotechnical properties of such failure surfaces are very difficult to be estimated due to the heterogeneous nature of these planes and back analysis is the best method to obtain reliable parameters. Back analysis results from two case studies showed significant differences to the laboratory test results. Finally, the concepts of the appropriate support measures based on the mechanism of failure of two case studies are presented in the paper.